Azimuthal Polarization Filtering for Accurate, Precise, and Robust Single-Molecule Localization Microscopy - Lew, Matthew D. (Nano Lett, 2014)
[Image: see text] Many single nanoemitters such as fluorescent molecules produce dipole radiation that leads to systematic position errors in both particle tracking and super-resolution microscopy. Via vectorial diffraction equations and simulations, we show that imaging only azimuthally polarized light in the microscope naturally avoids emission from the z-component of the transition dipole moment, resulting in negligible localization errors for all emitter orientations and degrees of objective lens misfocus. Furthermore, localization accuracy is maintained even in the presence of aberrations resulting from imaging in mismatched media.